Copper-Induced Overexpression of Genes Encoding Antioxidant System Enzymes and Metallothioneins Involve the Activation of Cams, Cdpks and Mek1/2 in the Marine Alga Ulva Compressa - Moenne-Munoz, A; Laporte-Poblete, D; Gonzalez-Figueroa, A; Valdes-Parra, N; Navarrete-Rosales, A (Elsevier B.V., 2016)
Transcriptomic analyses were performed in the green macroalga Ulva compressa cultivated with 10 μM copper for 24 h. Nucleotide sequences encoding antioxidant enzymes, ascorbate peroxidase (ap), dehydroascorbate reductase (dhar) and glutathione reductase (gr), enzymes involved in ascorbate (ASC) synthesis L-galactose dehydrogenase (l-gdh) and L-galactono lactone dehydrogenase (l-gldh), in glutathione (GSH) synthesis, γ-glutamate-cysteine ligase (γ-gcl) and glutathione synthase (gs), and metal-chelating proteins metallothioneins (mt) were identified. Amino acid sequences encoded by transcripts identified in U. compressa corresponding to antioxidant system enzymes showed homology mainly to plant and green alga enzymes but those corresponding to MTs displayed homology to animal and plant MTs. Level of transcripts encoding the latter proteins were quantified in the alga cultivated with 10 μM copper for 0–12 days. Transcripts encoding enzymes of the antioxidant system increased with maximal levels at day 7, 9 or 12, and for MTs at day 3, 7 or 12. In addition, the involvement of calmodulins (CaMs), calcium-dependent protein kinases (CDPKs), and the mitogen-activated protein kinase kinase (MEK1/2) in the increase of the level of the latter transcripts was analyzed using inhibitors. Transcript levels decreased with inhibitors of CaMs, CDPKs and MEK1/2. Thus, copper induces overexpression of genes encoding antioxidant enzymes, enzymes involved in ASC and GSH syntheses and MTs. The increase in transcript levels may involve the activation of CaMs, CDPKs and MEK1/2 in U. compressa. © 2016 Elsevier B.V.